Digitalisation, unions and participation: the German case of 'industry 4.0'. Issue 3 (11th June 2020) - Haipeter, Thomas
Abstract: This article tackles the question of how labour representatives cope with the implementation of 'Industrie 4.0' in German manufacturing plants. Digitalisation of manufacturing is going along with challenges for employment, work organisation and working conditions. The article analyses one of the main strategies German unions have developed, the project 'Work 2020', which was to raise works councils' awareness of the workplace impact of digitalisation, improve their knowledge of the changes, raise their capacity to respond and, finally, lead to the negotiation of workplace agreements on this issue with employers. The results of the analysis show that a strong interplay between unions and works councils and the activation of works councils by the unions have become indispensable preconditions for coping with the new challenges both of digitalisation and of the ongoing erosion of the German system of labour relations.